Análisis jurídico sobre el derecho de visitas a los hijos, estudio de casos de retención indebida en el cantón Arenillas, provincia de El Oro, periodo 2010-2012. - Herrera Enríquez, Diego Vinicio (2013)
When family normally breaks down and comes the marriage crisis, take relevacia is one of the most delicate, because in most cases are the children who suffer most the consequences of separation, altered the security sphere which until then they had.